Retábulo – Casa de Santos - Salteiro, Ilídio, 1953- (2014)
The altarpiece is a sanctuary that is present within all churches. It can be done with multiple possibilities, according to the circumstances of the place, and the aesthetic of the times and people. But after Vaticano II the altarpiece is no longer a formal element essential to liturgy and away leading role of liturgies, came to be regarded as a luxury and therefore only with cultural and heritage value